2021
DOI: 10.1007/s13239-021-00596-x
|View full text |Cite|
|
Sign up to set email alerts
|

Predictive Model for Thrombus Formation After Transcatheter Valve Replacement

Abstract: Purpose-Leaflet thrombosis is a significant adverse event after transcatheter aortic valve (TAV) replacement (TAVR). The purpose of our study was to present a semi-empirical, mathematical model that links patient-specific anatomic, valve, and flow parameters to predict likelihood of leaflet thrombosis. Methods-The two main energy sources of neo-sinus (NS) washout after TAVR include the jet flow downstream of the TAV and NS geometric change in volume due to the leaflets opening and closing. Both are highly depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…The blood flow inside the coronary arteries was simulated using similar 3-D FSI set-up as described in our previous works 18 , 19 , using open-source FOAM-Extend library 64 . The transcatheter aortic valve (TAV) frame and aortic wall are assumed to be rigid during diastole 65 , 66 . All details about governing equations, FSI method and modeling were presented in Supplementary Materials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood flow inside the coronary arteries was simulated using similar 3-D FSI set-up as described in our previous works 18 , 19 , using open-source FOAM-Extend library 64 . The transcatheter aortic valve (TAV) frame and aortic wall are assumed to be rigid during diastole 65 , 66 . All details about governing equations, FSI method and modeling were presented in Supplementary Materials.…”
Section: Methodsmentioning
confidence: 99%
“…However, we acknowledge that this a limitation of our study and we addressed this in the limitation section. Yet, it is worth mentioning that in the absence of essential characterization of patient-specific material properties required for FSI simulation of valve flow (which is the case in all ongoing FSI simulations 69 , 72 , 73 ), the results of FSI simulation could be an incorrect representative of the flow 66 . Therefore, whether the FSI simulation of the valve and aorta with such limitations improves the results is still debatable especially if the end goal is to provide a patient-specific framework 74 .…”
Section: Methodsmentioning
confidence: 99%
“…A common finding in CFD simulations is the presence of stagnant regions in the aortic sinus, in which blood clots are thought to form. Hatoum et al [17] combined a CFD model of flow through patient specific geometry post-TAVR with a reduced order model that predicted thrombus growth based on the wall shear stress and percent stasis volume measurements. While they were able to determine a correlation between circulation and amount of thrombosis, they concluded that finer flow metrics or FSI analysis are needed to fully predict thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…SLT is a complicated phenomenon that depends on numerous indicators, such as valve and root anatomy [ 2 ], haemodynamics [ 3 , 4 ], age of the patient [ 5 ], medication history [ 5 ], valve type (bicuspid or tricuspid), and valve size [ 6 ]. For instance, we would like to note that according to our most recent dimensional analysis study, we showed that the coronary artery ostia locations, mean jet velocity, area of the neo-sinus opening, cross-sectional area of neo-sinus, ejection time and flow separated area (area between the valve stent and the aortic wall) significantly impact the risk of SLT [ 2 ]. We showed that all these parameters can be grouped into 1 nondimensional parameter called normalized circulation.…”
mentioning
confidence: 99%
“…We showed that all these parameters can be grouped into 1 nondimensional parameter called normalized circulation. Normalized circulation is a fast predictor of the risk of thrombus formation [ 2 ]. The method we have developed can be applied prior to the transcatheter aortic valve replacement and assist in finding the optimum replacement location and expansion degree to minimize the risk of SLT [ 2 ].…”
mentioning
confidence: 99%